Numerical Simulation of Variable-Speed Propulsion Characteristics of Bionic Undulating Fins - Chuanxin XU; Guijie LIU; Penglei MA; Guanghao LI; Bing YAO; Jiajun ZENG (水下无人系统学报)
The hydrodynamic performance of bionic undulating fin robots is crucial for their precise control. This paper investigated the hydrodynamic response mechanism of the undulating fin during acceleration and deceleration through numerical simulation, revealing the relationship between the propulsive force and control frequency at variable-speed stages. The results show that at the acceleration stage, when the frequency increases from low to high, the vortices remaining at the low-frequency stage merge with newly generated vortices at the high-frequency stage, resulting in a propulsive force higher than steady value, which can be controlled by appropriately increasing the frequency; at the deceleration stage, when the frequency drop is small, the lagging vortices come off too late, producing a long period of irregular higher propulsive force, and the frequency gradient can be appropriately reduced to minimize this effect. This effect is significantly reduced when the frequency drop is too large. This research can provide theoretical support for the precise control of bionic undulating fin robots during speed changes, contributing to the improvement of control system stability.